Exploring The Sequence of Electron Density Along The Chemical Reactions Between Carbonyl Oxides And Ammonia/Water Using Bond Evolution Theory. Issue 17 (28th July 2021) - Adjieufack, Abel Idrice; Bake, Maraf Mbah; Nguimkeu, Charnel Nguemo; Pilmé, Julien; Ndassa, Ibrahim Mbouombouo
Abstract: The molecular mechanism of the reactions between four carbonyl oxides and ammonia/water are investigated using the M06‐2X functional together with 6‐311++G(d, p) basis set. The analysis of activation and reaction enthalpy shows that the exothermicity of each process increased with the substitution of electron donating substituents (methyl and ethenyl). Along each reaction pathway, two new chemical bonds C−N/C−O and O−H are expected to form. A detailed analysis of the flow of the electron density during their formation have been characterized from the perspective of bonding evolution theory (BET). For all reaction pathways, BET revealed that the process of C−N and O−H bond formation takes place within four structural stability domains (SSD), which can be summarized as follows: the depopulation of V(N) basin with the formation of first C−N bond (appearance of V(C, N) basin), cleavage of N−H bond with the creation of V(N) and V(H) monosynaptic basin, and finally the V(H, O) disynaptic basin related to O−H bond. On the other hand, in the case of water, the cleavage of O−H bond with the formation of V(O) and V(H) basins is the first stage, followed by the formation of the O−H bond as a second stage, and finally the creation of C−O bond. Abstract : An analysis of electron density along the mechanisms of carbonyl oxide and ammonia/water has been characterized from the perspective of bonding evolution theory (BET). BET reveals that the C−N bond formation takes place first and followed by O−H one along the reaction pathway of ammonia while the formation of new chemical bonds (C−O and O−H) is simultaneous in case of water.